The effect of Npl on ROA and ROE Moderated by GCG at BPR BKK Purwodadi - Moh Arwan Hamidi; Enny Susilowati Mardjono (Jurnal Telekomunikasi dan Informatika, 2026)
This study examines the effect of Non-Performing Loans (NPL) on bank profitability, measured by Return on Assets (ROA) and Return on Equity (ROE), and investigates the moderating role of Good Corporate Governance (GCG) in the relationship between credit risk and profitability at PT BPR BKK Purwodadi (Perseroda). This research employs a quantitative approach using panel data obtained from 18 branch offices over the 2020–2024 period, resulting in 90 observations. The data were analyzed using Moderated Regression Analysis (MRA). The findings reveal that NPL has a negative and statistically significant effect on both ROA and ROE, indicating that increasing credit risk reduces the bank's ability to generate profits from its assets and shareholders equity. However, Good Corporate Governance does not significantly moderate the relationship between NPL and either ROA or ROE, suggesting that the implementation of governance practices has not been sufficient to mitigate the adverse impact of credit risk on profitability. These findings highlight that effective credit risk management remains the primary determinant of banking profitability, while governance mechanisms alone are insufficient to improve financial performance without being supported by sound credit management practices. This study contributes to the banking literature by providing empirical evidence on the relationship between credit risk, corporate governance, and profitability in Indonesian rural banks. The findings also provide practical implications for bank management in strengthening credit assessment, borrower monitoring, internal control systems, and governance implementation to enhance sustainable financial performance. Keywords: Non-Performing Loans; Return on Assets; Return on Equity; Good Corporate Governance; Banking Profitability.